AYAT-AYAT TENTANG RELASI LAKI-LAKI DAN PEREMPUAN DALAM AL-QURâAN: Analisis Struktural Levi-Strauss - Fauziah, Nur (Al-Ahwal, 2015)
Religion is a social institution, especially for the Muslim community in general, determine the dynamics of the entire development community. In many cases the social processes that marginalizing women, intentionally or not, often involving religion as elements forming knowledge about relationships between men and women are unequal, and often used as a source of theological legitimacy of the above indisputable fact that marginalize women. During this time, the field of study of the Qurâan many scholars dominated philology and history. This led to a prolonged confusion between the text and the history of salvation history, which is implicit in it. This needs to be solved, with the view that the text of the Quran and his commentary as an expression of the views of Islam. This is where the importance of the legacy of structuralism in a given interpretation. By using Levi-Strauss structuralism, an attempt to determine the relationship webs in the narrative, the relationship is either syntagmatic or paradigmatic, to find hidden messages or messages that are deepest in the verses of the Qurâan.